Augmentation of Pesticide in Activated Sludge - Maisarah Ab Rahman (School of Environmental Engineering, University Malaysia Perlis, 2016)
To compare the effect of different concentration of metaldehyde on the microbial growth in activated sludge. To study the growth profile of microorganisms in optimum pesticide. To study the physiochemical factors that affect degradation of pesticide in activated sludge.